The Tumor Immunoenvironment - Shurin, Michael R.; Umansky, Viktor.; Malyguine, Anatoli. (Springer Netherlands : Imprint: Springer, 2013)
Interaction between malignant cells and their surrounding tissue plays a crucial role in tumor growth, invasiveness and spreading to the distant organs. New findings provide evidence of a principal importance of the immune cells for controlling this interaction and orchestrating multiple events in the tumor microenvironment. The balance between immune cells that support tumor progression and immune cells that sustain tumor-controlling immune surveillance is tightly regulated by various factors originated from both the malignant and non-cancerous cells in the tumor microenvironment. Analysis of multidirectional immunological responses at the tumor site allows forming a new concept of The Tumor ImmunoEnvironment, which is introduced and discussed in the present book with a particular focus on the role of immune cells in controlling the tumor microenvironment at different stages of cancer development. The main goal of this publication is to provide an overview of the current knowledge on the complex and unique role of the immune system, tumor-associated inflammation and tumor-mediated immunomodulation in cancer progression in a way that allows understanding the logistics of cellular and molecular interactions in the tumor lesions. Moreover, it is discussed how these interactions evolve during cancer progression and in response to different kinds of anticancer therapy. It is anticipated that the book will attract many researchers and clinicians in the field of basic and applied tumor immunobiology and open new opportunities for collaborative programs aiming at the development of effective and feasible therapeutic approaches to cancer treatment.